2010
DOI: 10.1002/cne.22423
|View full text |Cite
|
Sign up to set email alerts
|

Inherited neuroaxonal dystrophy in dogs causing lethal, fetal‐onset motor system dysfunction and cerebellar hypoplasia

Abstract: Neuroaxonal dystrophy in brainstem, spinal cord tracts, and spinal nerves accompanied by cerebellar hypoplasia was observed in a colony of laboratory dogs. Fetal akinesia was documented by ultrasonographic examination. At birth, affected puppies exhibited stereotypical positioning of limbs, scoliosis, arthrogryposis, pulmonary hypoplasia, and respiratory failure. Regional hypoplasia in the central nervous system was apparent grossly, most strikingly as underdeveloped cerebellum and spinal cord. Histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…In dogs, NAD has previously been reported in several breeds, such as Rottweilers [9–11], Collie sheepdogs [12], Papillons [1316], Giant Schnauzer-Beagle crossbreeds [18], Jack Russell terriers [19], Spanish Water dogs [20], and a Dachshund-cross dog [21]. Among these, genetic studies have been extensively performed for a few breeds, and only two forms of canine NAD have been characterized at the molecular level: a mitofusin 2 (MFN2) missense mutation with foetal onset NAD in laboratory dogs [18] (Giant Schnauzer-Beagle crossbreed) and a TECPR2 missense mutation in Spanish Water dogs [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dogs, NAD has previously been reported in several breeds, such as Rottweilers [9–11], Collie sheepdogs [12], Papillons [1316], Giant Schnauzer-Beagle crossbreeds [18], Jack Russell terriers [19], Spanish Water dogs [20], and a Dachshund-cross dog [21]. Among these, genetic studies have been extensively performed for a few breeds, and only two forms of canine NAD have been characterized at the molecular level: a mitofusin 2 (MFN2) missense mutation with foetal onset NAD in laboratory dogs [18] (Giant Schnauzer-Beagle crossbreed) and a TECPR2 missense mutation in Spanish Water dogs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, genetic studies have been extensively performed for a few breeds, and only two forms of canine NAD have been characterized at the molecular level: a mitofusin 2 (MFN2) missense mutation with foetal onset NAD in laboratory dogs [18] (Giant Schnauzer-Beagle crossbreed) and a TECPR2 missense mutation in Spanish Water dogs [20]. However, the causal mutations of the other forms of canine NAD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Using a genetic linkage-based approach and gene expression analysis, we demonstrated that a novel homozygous mutation of the MFN2 gene causes lethal, autosomal recessive FNAD in dogs [10]. Familial NAD has been described in dogs previously [2935], but none have been of obviously fetal-onset, nor has a canine NAD-causing mutation been determined before.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal swellings of affected pups were filled with membrane bound fragments of variably degenerated mitochondria and other tubulomembranous material embedded in disorganized whorls of neurofilaments [10]. This pathology is similar to that in human patients exhibiting INAD caused by PLA2G6 mutations or neurodegeneration with brain iron accumulation (NBIA1; a.k.a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation